2021
DOI: 10.2147/rmhp.s316429
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Air Pollution and Osteoporosis: A Systematic Review

Abstract: Air pollution is associated with inflammation and oxidative stress, which predispose to several chronic diseases in human. Emerging evidence suggests that the severity and progression of osteoporosis are directly associated with inflammation induced by air pollutants like particulate matter (PM). This systematic review examined the relationship between PM and bone health or fractures. A comprehensive literature search was conducted from January until February 2021 using the PubMed, Scopus, Web of Science, Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 113 publications
(241 reference statements)
1
10
0
Order By: Relevance
“…A recent meta-analysis reported inconsistent associations between PM exposure and osteoporosis risk or fractures but attributed it to heterogeneous study designs, participant characteristics, and analyses. 50 While air pollution studies are indeed heterogeneous, results from our studies are consistent and suggest that thousands of aging populations may be affected around the globe, particularly by gases like NO 2 that were not included in previous analyses of particulate matter.…”
Section: Discussionsupporting
confidence: 70%
“…A recent meta-analysis reported inconsistent associations between PM exposure and osteoporosis risk or fractures but attributed it to heterogeneous study designs, participant characteristics, and analyses. 50 While air pollution studies are indeed heterogeneous, results from our studies are consistent and suggest that thousands of aging populations may be affected around the globe, particularly by gases like NO 2 that were not included in previous analyses of particulate matter.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, SO 2 and resulting pollutants can travel large distances far from the emission sources affecting a large number of residents [ 35 ]. SO 2 is generally highly correlated with other air pollutants, especially NO 2 and PM, which were positively correlated with osteoporosis in previous studies [ 36 ]. During the study period, high SO 2 emission and SO 2 concentrations were consistently observed in four of our seven target cities (e.g., Daejeon, Ulsan, Incheon, Busan) in our study, which contain many fossil-fuel-burning plants located at seaports and industrial complexes [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 79%
“…Environmental pollution was an important factor causing the decline of respiratory system function and leading to osteoporosis. Environmental pollutants related to the development of osteoporosis mainly included the particles with diameter <2.5 μm (PM 2.5 ) and automobile exhaust ( Chen et al, 2015 ; Pang et al, 2021 ). Previous studies reported that decreased spinal bone mineral density could be observed after exposure to PM 2.5 ( Ranzani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 was positively correlated with serum RANKL and the osteoclast precursor CD14 (+) CD16 (+) monocytes ( Saha et al, 2016 ). Additionally, PM 2.5 could induce the secretion of inflammatory cytokines such as TNF-α, IL-1β, and IL-6, all of which were stimulators of bone resorption ( Pang et al, 2021 ). Additionally, vitamin D was deficient with PM 2.5 exposure ( Afsar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%